Three-Dimensional Simulation of the Entrance-Impeller Interaction of a Hydraulic Disc Pump - Pérez, José Leonardo; Patiño Carrillo, Luis; Espinoza, Henry (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>A study of the fluidynamic behavior of the entrance-impeller interaction of a Hydraulic Disc Pump is presented, through numerical simulations, using the finite volume method. A three-dimensional numerical model was developed, using the technique of multiblocks and structured meshes, by means of the commercial code CFX 4.3TM. The simulated model corresponds the flat impeller of (203 mm) of diameter to the exit, of a disc pump of simple suction. 8 flows were simulated, in those that the nominal flow, the maximum flow and the minimum flow were included. The simulations were carried out in stationary state and it took advantage the periodic condition of the flow inside the impeller, being reduced to section Â¼. The obtained load-flow curve was compared with the experimental pump curve given by the maker. The obtained curve, through the numerical results of the simulations, possesses a similar behavior to the experimental one, with values of load superiors to 15%, for the near flows to the nominal one. Additionally, the interaction entrance-impeller was analyzed through of pressure and velocities profiles, that which allowed to know and to understand the behavior of these variables for the simulated conditions